Peranan Pinandita Dalam Upacara Panca Yajña - Gede Indra Nisastra; Ketut Sudiartha; I Made Hartaka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The saint is someone who is very influential in the smooth implementation of the Hindu Yajña ceremony. Saints can be grouped into two groups, namely Eka Jati and Dwi Jati. Each class of saints certainly has a different role and authority in leading the implementation of the Yajña ceremony. In the implementation of the Panca Yajña ceremony, of course, the Saints have an important role, without the Saints, the ceremony held will not be completed. Saints have had an important role since ancient times, starting from spreading the teachings of Hinduism, compiling Hindu scriptures, and leading religious ceremonies until now. The holy person who has carried out the mewinten ceremony is called Pandita (stakeholder) and the holy person who has carried out the medical ceremony is called Pinandita (sulinggih).